Research methods in education - Cohen, Louis 1928-; Manion, Lawrence; Morrison, Keith (Keith R. B.). (London New York Routledge, 2007)
This edition covers the whole range of methods currently employed by educational research at all stages. It includes new material on complexity theory, ethics, sampling, and sensitive educational research.
Includes bibliographical references (pages [593]-632) and index.
Keywords: Education -- Research; Education -- Research -- Great Britain